(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
It is known that today the construction industry is regarded as one of the main directions in the formation of small business and private entrepreneurship, socio-economic development, development of the property class and competition in the market, and today it serves as a locomotive for sustainable economic development. The article assesses the role of large and small businesses in ensuring the development of the country’s construction industry, summarizes the best world and domestic experience in this area, and also develops proposals and recommendations for the further development of this industry.